Spontaneous and Acetylcholine Evoked Calcium Transients in the Developing Mouse Utricle - Holman, Holly A.; Poppi, Lauren A.; Frerck, Micah; Rabbitt, Richard D. (Frontiers in Cellular Neuroscience, 2019)
Spontaneous calcium transients are present during early postnatal development in the mouse retina and cochlea, and play an important role in maturation of the sensory organs and neural circuits in the central nervous system (CNS). It is not known whether similar calcium transients occur during postnatal development in the vestibular sensory organs. Here we demonstrate spontaneous intracellular calcium transients in sensory hair cells (HCs) and supporting cells (SCs) in the murine utricular macula during the first two postnatal weeks. Calcium transients were monitored using a genetically encoded calcium indicator, GCaMP5G (G5), at 100ms-frame-1 in excised utricle sensory epithelia, including HCs, SCs and neurons. The reporter line expressed G5 and tdTomato (tdT) in a Gad2-Cre dependent manner within a subset of utricular HCs, SCs and neurons. Kinetics of the G5 reporter limited temporal resolution to calcium events lasting longer than 200ms. Spontaneous calcium transients lasting 1-2 s were observed in the expressing population of HCs at birth and slower spontaneous transients lasting 10-30 s appeared in SCs by P3. Beginning at P5, calcium transients could be modulated by application of the efferent neurotransmitter acetylcholine (ACh). In mature mice, calcium transients in the utricular macula occurred spontaneously, had a duration 1-2 s, and could be modulated by the exogenous application of acetylcholine (ACh) or muscarine. Long-lasting calcium transients evoked by ACh in mature mice were blocked by atropine, consistent with previous reports describing the role of muscarinic receptors expressed in calyx bearing afferents in efferent control of vestibular sensation. Large spontaneous and ACh evoked transients were reversibly blocked by the inositol trisphosphate receptor (IP3R) antagonist aminoethoxydiphenyl borate (2-APB). Results demonstrate long-lasting calcium transients are present in the utricular macula during the first postnatal week, and that responses to ACh mature over this same time period.